A Generalized Darbo-Type Fixed Point Theorem Using Monotonicity in Partially Ordered Banach Spaces with Application to Integral Equation (International Journal of Scientific Research in Science and Technology, 2025)
In this paper, we establish a generalized Darbo-type fixed point theorem for monotone operators in partially ordered Banach spaces. The theorem extends classical fixed point results by incorporating measures of noncompactness and monotonicity with respect to the order structure. The theorem is successfully applied to demonstrate the existence of solution for integral equation.